The Lynching of Architecture - Rappaport, Alexander (project baikal, 2018)
“The Image of the City” by Kevin Lynch gave rise to the environmental approach, which expressed demographic values. In the environmental approach, architecture of a separate structure merged with the city, losing its aristocraticism and transcendental isolation. The word “lynching” is used in wordplay and means a democratic trial of the aristocratic architecture. The environmental approach results in the death of architecture.